Leadership Style with Paramedic Work Motivation on General Hospital Performance - Natalia Natalia; Edy Fachrial; Suandy Suandy; Yohani Theresia; I Nyoman Ehrich Lister (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study examines the influence of leadership style and paramedic work motivation on the performance of general hospitals. The research aims to investigate how leadership approaches and motivation levels among paramedics affect hospital outcomes. Using a quantitative approach, data was collected from paramedics working in several general hospitals. The analysis included statistical methods such as regression analysis and mediation analysis to test the direct and indirect effects of leadership style and work motivation on hospital performance. The results showed that leadership style and work motivation significantly affect hospital performance. Specifically, effective leadership and high work motivation among paramedics contributed to improved hospital performance indicators. This study provides insights into how hospital management can improve performance by focusing on leadership development and motivation enhancement strategies. The findings highlight the importance of fostering a supportive leadership environment and promoting work motivation among paramedics to achieve better hospital performance.